EDUKASI KORELASI ANEMIA DENGAN POLA KONSUMSI FE PADA REMAJA, DI PONDOK PESANTREN JAMILURRAHMAN, WIROKERTEN, BANGUNTAPAN, BANTUL - Arviani, Arviani (LPPM STIKES Madani, 2023)
Pondok Putri Ma'had Jamilurrahman As-Salafy Yogyakarta in Banguntapan, Bantul is specifically for women's tadribut du'at (da'i training). The students at this lodge are 15 – 24 years old, are junior high and high school graduates from various regions throughout Indonesia. The background of graduates from public schools and Islamic boarding schools. Hb measurement data for 105 students at Pondok Putri Ma'had Jamilurrahman As-Salafy showed 39% had anemia with details of severe anemia (<7.0 g/dl) 3%, moderate anemia (7.0 - 9.9 g/dl) by 10% and mild anemia (10.00 – 11.9 g/dl) by 27%. Counseling about health is rarely done in this pesantren, so this community service is to provide education about the importance of diet and regular iron consumption, especially for young women. Providing education in the form of measuring Hb levels and counseling. The problem of iron intake and diet that supports iron absorption has not been a major concern and focus in adolescent girls. Adolescents who suffer from anemia tend to get tired easily, tired and lethargic. Patients with anemia also tend to lack interest in learning which can affect academic achievement. The community service approach used is community empowerment. Technical implementation for 1 day. The output target of this activity is to reduce the risk factors for anemia due to iron deficiency by consuming iron regularly.